2020
DOI: 10.1007/s12020-020-02233-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of acylated ghrelin in patients with insulinoma and expression of ghrelin and its receptor in insulinomas

Abstract: Background Insulinoma is a subtype of pancreatic neuroendocrine tumors. Many patients with insulinoma are obese due to frequent food intake. Ghrelin is associated with obesity and blood levels of insulin. It is not clear if plasma levels of ghrelin in insulinoma patients correlate with hyperinsulinemia and obesity. Expression of ghrelin and its receptor has not been well demonstrated in insulinoma. Objective To study if plasma levels of ghrelin is associated with obesity and hyperinsulinemia or hyperproinsulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Similarly, a recent study demonstrated that circulating AG levels are reduced in patients with insulinoma 146 . Patients with these neuroendocrine tumours often present insulin over secretion, which has been suggested to reduce gastric ghrelin release 146 . However, patients with insulinoma are frequently obese 147 .…”
Section: Peripheral Mechanisms Modulating Postprandial Ghrelin Secretmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, a recent study demonstrated that circulating AG levels are reduced in patients with insulinoma 146 . Patients with these neuroendocrine tumours often present insulin over secretion, which has been suggested to reduce gastric ghrelin release 146 . However, patients with insulinoma are frequently obese 147 .…”
Section: Peripheral Mechanisms Modulating Postprandial Ghrelin Secretmentioning
confidence: 98%
“…Therefore, a secretory interaction between these glucoregulatory hormones seems reasonable, with most clinical studies reporting an inhibitory effect of insulin on TG release 127‐129 . Similarly, a recent study demonstrated that circulating AG levels are reduced in patients with insulinoma 146 . Patients with these neuroendocrine tumours often present insulin over secretion, which has been suggested to reduce gastric ghrelin release 146 .…”
Section: Peripheral Mechanisms Modulating Postprandial Ghrelin Secretmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghrelin and the type 1a ghrelin receptor (GHS-R1A) are expressed in different types of neuroendocrine tumors. Recently, Wu et al [ 16 ] found that GHS-R1a was found in 60% of insulinomas, suggesting that ghrelin may act through autocrine or paracrine pathways. The proliferative effects of ghrelin and its association with insulinoma have not been studied, although there is a clinical case report where a ghrelin-producing neuroendocrine tumor was transformed into an insulinoma[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with insulinomas are often more obese, probably because of hunger or because preventing hypoglycemia prompts patients eating frequency. [33] Blood lipid levels in obese patients are characterized by increased LDL and triglyceride as well as decreased HDL in serum. [34,35] A representative survey enrolling 163,641 adults shows that women were associated with a risk of high LDL, and people older than 60 have higher TC levels.…”
Section: Discussionmentioning
confidence: 99%